Del telescopio hacia la autocomprensión: el libre juego de escalas de Paul Ricoeur y sus implicaciones en el compromiso social del historiador - Neves Guzmán, Camila (Historiografías, 2021)
This work identifies the idea of ​​the free game of scales, developed by the philosopher Paul Ricoeur, as the rescue of subaltern voices by historians, who have defined the social and political commitment of history in the self-knowledge of current social agents. The free game of scales as an action of methodological freedom has allowed the deployment of novel objects of singular studies that grant flexibility, many-sided values, and differentiation to history through the dialectic of representation. These elements allow for the weaving of useful interpretations that serve to reflect on the inequalities invaded by the discourse of modernity, understanding popular culture and its microstructures from the variation of scales.